Identification of Familial Infections Using Multilocus Microsatellite Typing in Tinea Corporis due to Microsporum canis: A Case Report - Takahashi, Chiaki; Asakura, Ryohei; Chaya, Ayaka; Ota, Michi; Harada, Kazutoshi; Inukai, Tatsuya; Nakamura, Shigeki; Hata, Yasuki; Watanabe-Okada, Emiko (Medical Mycology Journal, 2024)
Microsporum canis is a type of dermatophyte that causes zoonotic dermatophytosis in cats and dogs. We report three cases of tinea corporis due to M. canis from a single household with a domestic cat as a pet. The cases included a woman in her thirties (mother), a girl in her teens (older sister), and a girl in her teens (younger sister). Following sudden hair loss in the domestic cat, annular erythema with pruritus and scales appeared on the face, neck, and limbs of the older sister, younger sister, and mother, sequentially; they subsequently visited our hospital. Potassium hydroxide direct microscopy revealed filamentous fungi on all three women. In addition, short-haired colonies with a white to yellowish-white color and extending in a radial manner were found in cultures using a flat plate agar medium. A slide culture with the same medium indicated pointed spindle-shaped macroconidia with 7-8 septa. Therefore, the cases were diagnosed as tinea corporis due to M. canis. Genetic analysis of the cells of the cat and the mother, older sister, and younger sister using multilocus microsatellite typing (MLMT) indicated that all cases were classified into the same genotype, suggesting that the transmission route of these cases was familial. Here, we show that MLMT is useful in identifying the infection route in cases of tinea corporis due to M. canis.